Properties of Plywood Made of Thermally Treated Veneers Bonded with Castor Oil-Based Polyurethane Adhesive - Galdino, Danilo Soares [UNESP]; Silva, Maria Fernanda Felippe [UNESP]; Arroyo, Felipe Nascimento; Rangel, Elidiane Cipriano [UNESP]; Caraschi, José Cláudio [UNESP]; Santos, Herisson Ferreira dos; de Freitas, Ludmila; Christoforo, André Luis; de Campos, Cristiane Inácio [UNESP] (MDPI, 2023)
Wood industries use thermal and thermomechanical treatments as ecological approaches to increase the durability of wood products, avoiding the need for chemical additives. In this regard, the aim of this study was to compare the physical and mechanical properties of plywood made from veneers treated at different temperatures using thermal and thermomechanical processes, with untreated panels serving as a control. The treatment process involved Pinus taeda veneers submitted to treatment in a hot press at 1.0 MPa in a laboratory oven at temperatures of 160 °C, 180 °C, and 200 °C for 30 min. For bonding the veneers, a vegetable-based polyurethane resin derived from castor oil with a grammage of 395 g/m2 was used, applying pressing conditions at 90 °C, 0.6 MPa, and 10 min. Our results indicate that temperature significantly influences plywood properties, playing a key role in the choice of equipment for the treatment process. Regardless of the method employed, the treatment resulted in an improvement in the hydrophobicity of the veneers due to the decrease in hemicellulose content. Notably, the reduction in strength and stiffness caused by the loss of cell wall polymers was not statistically significant. The treatment was successful in softening the wood material, reducing roughness, and increasing wettability. Despite a minimum of 20% reduction in glue line tension, the samples still surpassed the 1 MPa mark, showing satisfactory results. This demonstrates the feasibility of adjusting treatment variables to ensure the proper use of this adhesive.
Keywords: chemical changes; mechanical properties; quality control; roughness; wettability; wood products